2016
DOI: 10.1158/0008-5472.can-15-2680
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Histone Deacetylase Activity in Malignant Melanoma Provokes RAD51 and FANCD2-Triggered Drug Resistance

Abstract: DNA-damaging anticancer drugs remain a part of metastatic melanoma therapy. Epigenetic reprogramming caused by increased histone deacetylase (HDAC) activity arising during tumor formation may contribute to resistance of melanomas to the alkylating drugs temozolomide, dacarbazine, and fotemustine. Here, we report on the impact of class I HDACs on the response of malignant melanoma cells treated with alkylating agents. The data show that malignant melanomas in situ contain a high level of HDAC1/2 and malignant m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 44 publications
6
61
0
Order By: Relevance
“…Inhibition of HDACs has been shown to abolish drug-resistance in cancer cells (36). In support of this finding, HDAC inhibition sensitizes neuroblastoma cells to the genotoxins etoposide, melphalan, carboplatin and vincristine (37), melanoma cells to temozolomide, psoralen and UVA, fotemustine and ionizing radiation (16,38,39), prostate cancer cells to bleomycin, doxorubicin, etoposide, hydroxyurea, cisplatin and ionizing radiation (40,41), breast cancer cells to etoposide and olaparib (42,43) and head and neck cancer cells to cisplatin (44). In addition, HDAC inhibition sensitizes squamous cell carcinoma, non-small cell lung cancer, osteosarcoma, rhabdomyosarcoma and cervical cancer cells to ionizing radiation (4548).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Inhibition of HDACs has been shown to abolish drug-resistance in cancer cells (36). In support of this finding, HDAC inhibition sensitizes neuroblastoma cells to the genotoxins etoposide, melphalan, carboplatin and vincristine (37), melanoma cells to temozolomide, psoralen and UVA, fotemustine and ionizing radiation (16,38,39), prostate cancer cells to bleomycin, doxorubicin, etoposide, hydroxyurea, cisplatin and ionizing radiation (40,41), breast cancer cells to etoposide and olaparib (42,43) and head and neck cancer cells to cisplatin (44). In addition, HDAC inhibition sensitizes squamous cell carcinoma, non-small cell lung cancer, osteosarcoma, rhabdomyosarcoma and cervical cancer cells to ionizing radiation (4548).…”
Section: Introductionmentioning
confidence: 88%
“…Apart from the role of SIRT1 in NER, the overexpressed HDACs in melanoma cells (16,26) (Table 1) seem to also play a role in stimulating NER, as HDAC inhibition by sodium butyrate, an inhibitor of class I and class IIA HDACs (84), inhibits removal of bulky lesions by NER in these cells (38). Contrary to melanoma cells, HDAC inhibition with sodium butyrate in normal human fibroblasts enhances NER upon UV irradiation (85).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malignant melanomas in situ contain a high level of HDAC-1, 2 and malignant melanoma cells overexpress HDAC-1, -2, -3 compared with non-cancer cells. Furthermore, pharmacologic inhibition of class I HDAC sensitizes malignant melanoma cells to apoptosis following exposure to alkylating agents, while not affecting primary melanocytes (24)(25)(26). West et al (27) showed that the immune system is absolutely necessary for the anticancer effect of HDACI (9,11,24,28).…”
Section: Discussionmentioning
confidence: 99%